The story of Wamba : Julian of Toledo's Historia Wambae regis - Julianus, Saint, Bishop of Toledo, -690 (Book collections on Project MUSE., 2005)
The literary study focuses on the political vocabulary of the text, the ideological messages implicit in its various sources and models, and its unique combination of classical, late antique, and medieval elements."--Jacket